PENINGKATAN KEMAMPUAN MENYIMAK MELALUI MEDIA BUKU CERITA BERGAMBAR PADA ANAK DI PAUD BUAH HATI BUNDA KABUPATEN KAUR - Aniarti; Rismareni Pransiska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Listening ability is an important aspect in the language development of early childhood. However, there are still children who experience difficulties in listening, such as lack of focus when listening to stories, not understanding the content of the story, and difficulty answering simple questions related to the story being told. This study aims to determine the improvement of listening ability through picture storybooks in children at the Buah Hati Bunda PAUD in Kaur Regency. The research method used is Classroom Action Research (CAR) which was carried out in two cycles, where each cycle consists of four stages: planning, implementation, observation, and reflection. The research subjects were 12 children consisting of 7 boys and 5 girls. Data collection techniques were carried out through observation, documentation, and interviews, while data analysis used percentages. The results of the study showed an increase in children's listening ability in each cycle. In the pre-cycle, children's listening ability obtained a percentage of 38.8% with the category of Starting to Develop (MB), increased to 62.1% in the first cycle with the category of Developing According to Expectations (BSH), and increased again to 82.6% in the second cycle with the category of Developing Very Well (BSB). The results showed that children's listening skills increased by 43.8% from the initial to the final stage of the study. Based on these results, it can be concluded that the use of picture storybooks is effective in improving children's listening skills at the Buah Hati Bunda Early Childhood Education Center in Kaur Regency.